Management of emerging multidrug-resistant tuberculosis in a low-prevalence setting. (May 2015) - Catho, G.; Couraud, S.; Grard, S.; Bouaziz, A.; Sénéchal, A.; Valour, F.; Perpoint, T.; Braun, E.; Biron, F.; Ferry, T.; Chidiac, C.; Freymond, N.; et al.
Abstract: Multidrug-resistant (MDR) tuberculosis (TB) is an emerging concern in communities with a low TB prevalence and a high standard of public health. Twenty-three consecutive adult MDR TB patients who were treated at our institution between 2007 and 2013 were reviewed for demographic characteristics and anti-TB treatment management, which included surgical procedures and long-term patient follow-up. This report of our experience emphasizes the need for an individualized approach as MDR TB brings mycobacterial disease management to a higher level of expertise, and for a balance to be found between international current guidelines and patient-tailored treatment strategies.